Community empowerment in the Coastal Area of Banda Aceh City by Introducing Organic Waste Management for Generating Biofertilizer - Darwin; Bulan, Ramayanty; Putra, Bambang Sukarno; Rizal, Muhammad (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This community service aims to introduce organic agriculture in Banda Aceh's coastal area by converting organic wastes into biofertilizer to remediate tsunami-affected lands with high salinity and low nutrients. Method: The team designed and implemented a mobile bio-composter system capable of processing 150 kg of organic waste. Field observations and soil analyses were conducted to assess land conditions, followed by technology transfer to Gampong Pie community members. Practical Applications: The mobile bio-composter processes household, municipal, and agricultural waste while enabling community members to produce their own microbial inoculants. This technology supports economic empowerment through fertilizer production and sales, addressing critical land issues while creating new business opportunities. Conclusion: The initiative successfully produced a mobile bio-composter installation that converts organic waste into biofertilizer for remediating coastal critical lands, promoting sustainable organic agriculture development in tsunami-affected areas.